Hozon: architectural and urban conservation in Japan - Enders, Siegfried R. C. T.; Enders, Siegfried R. C. T.; Gutschow, Niels; Gutschow, Niels (Edition Axel Menges, 1998)
The articles for this publication were prepared in the context of - a Japanese-German co-operative programme in architectural - and urban conservation in 1996-1998. For the first time ever a - Western publication attempts to portray the Japanese practice - of repair - hozon - of historic structures.